The Effect of Glurenorm (Gliquidone) on Aorta in STZ Induced Diabetic Rats - (:unkn) unknown (KAFKAS UNIV, VETERINER FAKULTESI DERGISI, 2011)
Vascular diseases are one of the common complications of diabetes mellitus. In diabetes, increased free radical formation raises the incidence of atherosclerosis and cardiovascular diseases. Regardless of the type of diabetes, the objective of the therapy is to achieve normoglycemia and to prevent or delay the complications. Glurenorm (gliquidone) is one of the members of sulphonylurea group oral antidiabetics. Sulphonylurea oral antidiabetics act via stimulating insulin release from beta cells of the pancreas. Therefore, the aim of the study was to investigate the effect of glurenorm (gliquidone, 10 mg/kg) on the aorta of streptozotocin-induced diabetic rats in terms of nonenzymatic glycation, lipid peroxidation and reduced glutathione. Both diabetic and control group rats have taken the drug daily, until the end of the experiment, at day 42. Blood samples and aorta was taken from each rat at day 42. Blood glucose was measured by o-toluidine method. Glurenorm decreased the blood glucose and increased the body weights of diabetic rats. However, glurenorm did not decrease non-enzymatic glycation of aorta proteins in diabetic rats, but it decreased lipid peroxidation of aorta. Although the aorta lipid peroxidation level was decreased in glurenorm given diabetic rats, glutathione level did not increase. This may show that oxidative damage continues during the glurenorm treatment. Glurenorm also did not change the electrophoretic pattern of aorta proteins. The results indicate the usage of glurenorm is effective on decreasing of blood glucose but not on decreasing nonenzymatic glycation or oxidative damage in aorta samples of diabetic rats.
Keywords: Diabetes; Aorta; Glurenorm; Nonenzymatic glycation; Lipid peroxidation; Glutathione; OXIDATIVE STRESS; NAD(P)H OXIDASE; MELLITUS; APOPTOSIS; STIFFNESS